2017
DOI: 10.1371/journal.pone.0184526
|View full text |Cite
|
Sign up to set email alerts
|

High genetic diversity and demographic history of captive Siamese and Saltwater crocodiles suggest the first step toward the establishment of a breeding and reintroduction program in Thailand

Abstract: The Siamese crocodile (Crocodylus siamensis) and Saltwater crocodile (C. porosus) are two of the most endangered animals in Thailand. Their numbers have been reduced severely by hunting and habitat fragmentation. A reintroduction plan involving captive-bred populations that are used commercially is important and necessary as a conservation strategy to aid in the recovery of wild populations. Here, the genetic diversity and population structure of 69 individual crocodiles, mostly members of captive populations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(69 citation statements)
references
References 52 publications
1
42
1
Order By: Relevance
“…Management of Chinese goral populations is important to guarantee their long-term survival in natural environments. To increase the Chinese goral population size, a captive breeding program is the only viable option because the species is almost extinct in the wild [11][12][13]. In 1993, a Chinese goral population was established outside their natural habitat (ex situ) at Omkoi Wildlife Breeding Center in Chiang Mai (17˚28'14.8", 98˚26'51.2"), Thailand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management of Chinese goral populations is important to guarantee their long-term survival in natural environments. To increase the Chinese goral population size, a captive breeding program is the only viable option because the species is almost extinct in the wild [11][12][13]. In 1993, a Chinese goral population was established outside their natural habitat (ex situ) at Omkoi Wildlife Breeding Center in Chiang Mai (17˚28'14.8", 98˚26'51.2"), Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…Maintenance of genetic diversity and demographic security are the primary goals for longterm conservation-population management. High genetic variation is the basis for adaptive evolution and survival and should be retained to promote the fitness of both individuals and the population [11][12][13]. By contrast, deleterious effects of inbreeding frequently occur in small captive populations, leading to decline of fitness and inbreeding depression [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The wild population of Siamese crocodiles is thought to be less than 1,000 (Bezuijen et al, ; Ihlow et al, ). However, although over 1 million Siamese‐like crocodiles are known to reside in crocodile farms throughout Southeast Asia, their potential use for conservation and re‐introduction purposes has remained controversial, with their genomic purity in doubt (Daltry et al, ; Lapbenjakul et al, ; Sam et al, ; Simpson & Bezuijen, ). Decades of mixed pairings in captivity may have eroded the genomic purity of captive individuals to an unknown degree (Fitzsimmons et al, ; Sam et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Any efforts at Siamese crocodile conservation through captive breeding and re-introductions necessitate first a determination of the genomic purity of potential candidates for relocation (Fitzsimmons et al, 2002;Lapbenjakul et al, 2017;Sam et al, 2015), and second an assessment of the overall population-genomic diversity as well as genetic relatedness among them. In combination these measures can ensure a maximization of population-genomic diversity and a minimization of human-induced genetic introgression among individuals to be released into the wild (Lapbenjakul et al, 2017;Sam et al, 2015). In addition, an understanding of the genetic diversity and recent population history of wild populations of the F I G U R E 1 Map showing the distribution of the Siamese crocodile and sampling locations.…”
Section: Crocodylus Siamensismentioning
confidence: 99%
“…In this context, the Siamese crocodile ( Crocodylus siamensis ) may be regarded as a particularly attractive source for biologically active proteins, short peptides, and amino acids (Pakdeesuwan et al, ) as previous reports identified several proteins and peptides contained in crocodile blood to constitute the first line of innate immune defense protecting these animals against bacterial infection (Hoffman, Biscayne, Binah, & Tivan, ; Phosri et al, ). Although the Siamese crocodile is classified as critically endangered in the wild, the successful initiation of intensive breeding programs in Thailand aiming to conserve the species have created large captive populations in crocodile farms (Lapbenjakul et al, ). As a result, industrial crocodile farming in Thailand has experienced substantial growth in recent years to satisfy the increasing demand for crocodile‐based products, in particular meat and leather as the most valuable export commodities.…”
Section: Introductionmentioning
confidence: 99%